2019 International Joint Conference on Neural Networks (IJCNN) 2019
DOI: 10.1109/ijcnn.2019.8852116
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning for System Trace Restoration

Abstract: Most real-world datasets, and particularly those collected from physical systems, are full of noise, packet loss, and other imperfections. However, most specification mining, anomaly detection and other such algorithms assume, or even require, perfect data quality to function properly. Such algorithms may work in lab conditions when given clean, controlled data, but will fail in the field when given imperfect data. We propose a method for accurately reconstructing discrete temporal or sequential system traces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Restorer solves the intermediate problem of restoring missing elements in sequences of discrete data while entirely replacing the recurrent components of existing solutions. We demonstrate that such an approach leads to reduced model sizes, faster training times, and higher-quality reconstruction when compared to what we will refer to as ''the LSTM model'' described by Sucholutsky et al (2019).…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Restorer solves the intermediate problem of restoring missing elements in sequences of discrete data while entirely replacing the recurrent components of existing solutions. We demonstrate that such an approach leads to reduced model sizes, faster training times, and higher-quality reconstruction when compared to what we will refer to as ''the LSTM model'' described by Sucholutsky et al (2019).…”
Section: Introductionmentioning
confidence: 94%
“…There are also a number of data restoration methods that assume that all the data is available at once (Blend & Marwala, 2008;Leke, Marwala & Paul, 2015;Gondara & Wang, 2017;Beaulieu-Jones & Moore, 2017). However, in the context of data restoration specifically for discrete, streaming data it was only recently demonstrated that a simple LSTM model can be used to restore missing message IDs in automotive data (Sucholutsky et al, 2019).…”
Section: Data Restoration With Deep Learningmentioning
confidence: 99%
See 3 more Smart Citations